Modelling of heat and mass transfer in clothing considering evaporation, condensation, and wet conduction with case study. (15th January 2023) - Joshi, Ankit; Psikuta, Agnes; Annaheim, Simon; Rossi, René M.
Abstract: Over the past few decades, several models of heat and mass transfer have been based on the assumption of the homogeneous thickness (or absence) of the enclosed air layer contradicting the real-life scenario of the skin-clothing-environment system. To address this research gap, in this study, the comprehensive model for heat and mass transfer was developed which considers thermal phenomena such as evaporation, condensation, and the effect of liquid moisture on the thermal insulation of fabrics (wet conduction) along with sensible heat transfer mechanisms and effects of spatial heterogeneity of air layers. The coupling between heat and mass transfer in the modelling approach resulted in an accurate evaluation of the mass of evaporated liquid moisture and condensed water vapour in a skin-clothing-environment system. The developed model is systematically validated with an increasing level of spatial complexity using homogeneous and heterogeneous air layers with single-layer and multi-layer clothing ensembles. The model is validated for 21 different experimental cases covering various parameters that affect mass transfer such as enclosed air gap thickness (clothing fit), evaporative resistance (permeable, semi-permeable, and impermeable to water vapour), ambient temperature (−10 °C to 34 °C), and relative humidity (80% to 18.5%). Finally, the relevance of the model for product development is demonstrated by a case study about smart skiwear. The presented study provides detailed insights into individual heat and mass transfer mechanisms in the skin-clothing-environment system, which is very useful to develop an in-depth understanding about local heat transfer mechanisms and for designing and development of functional and protective clothing. Highlights: Heterogeneity of the air layer has a significant effect on latent heat transfer. The model systematically validated to demonstrate reliability and accuracy. Analysis of moisture content in fabric on total thermal insulation of clothing. Optimization of smart skiwear using the presented model as a case study.